Professor Stanisław Berger - the jubilee of 100th birthday - Krystyna Gutkowska; Anna Gronowska-Senger; Kazimiera Ćwiek-Ludwicka (National Institute of Public Health - National Institute of Hygiene, 2023)
Professor Stanisław Berger - Polish scientist, creator of human nutrition science, international authority, excellent lecturer, and consistent organizer of the nutritional scientific community - celebrates his 100th birthday. He was born on September 13, 1923. The history of Professor Stanisław Berger's long life is presented in this jubilee article.